Cardiovascular and metabolic responses during 30 minutes of treadmill exercise shortly after consuming a small, high-carbohydrate meal - Diboll, D. C.; Boone, W. T.; Lindsey, L. R. (International Journal of Sports Medicine, 1999)
Fourteen male endurance runners (VO2peak = 64.8 +/- 8.7 ml x kg(-1) x min(-1)) participated in this study to determine the cardiovascular and metabolic responses during 30 minutes of treadmill running at a moderate intensity soon after consuming a small, high-carbohydrate meal (CHO-M). In randomized order on separate days, subjects either consumed the CHO-M (2088 kJ; 77% carbohydrate) 15 minutes prior to running or they fasted (FAST). Data were collected for 5 minutes beginning at 5, 15, and 25 minutes of the 30-minute run. Heart rate (HR) was determined, a metabolic measurement cart was used to determine VO2 and respiratory exchange ratio (RER), and the CO2 rebreathing procedure (Collier plateau method) was used to determine cardiac output (Q). Statistical analyses indicated that the CHO-M did not affect HR, stroke volume, Q, VO2, or RER compared to FAST. However, all grouped CHO-M and FAST variables, except VO2, changed significantly across the 30-minute exercise session. These data suggest that a small, high-carbohydrate meal does not alter cardiovascular and metabolic function during moderate-intensity exercise in endurance-trained subjects.